The European Union: A Sui Generis Legal Order: Prospects for Development - Mathieu, Bertrand (Federalism as the Future of the Diverse EU?, 2025)
The first phase of our collective research focused on the concept of constitutional identity. This raised the question of how this identity could be defined and, if necessary, protected, in the light of the requirements linked to the participation of States in European Union bodies. The second phase of this research focuses on the nature of the European legal order. The first step is to identify the legal categories that may assist in characterising the European Union. The document setting the context for the research starts from the premise that the European Union, which has embarked on the road to federalism, is halfway along this path, and sets out the prospect of a European Union as a simple structure for cohabitation and cooperation between States. Between a federation and an alliance treaty, there is probably a middle path, a legal order that is no longer federal but confederal in nature. Confederation means maintaining and guaranteeing the sovereignty of the confederate States. In any case, it seems advisable not to lock ourselves a priori in pre-established legal categories which may prove obsolete or inappropriate. As a first step of this approach, however, it is worth considering the nature of the European Union, resulting from the current Treaties. Secondly, it is noteworthy how the European Union uses integration mechanisms which go beyond a strict interpretation of the Treaties, with particular reference to the rule of law and the Union’s values. Finally, the third phase of the study will seek to consider the possible transformations of European institutions in a direction that is more respectful of State sovereignty. Keywords: European constitutionalism, federalism vs confederation, state sovereignty, CJEU, democratic legitimacy, rule of law.